Regiospecific Introduction of Halogens on the 2-Aminobiphenyl Subunit Leading to Highly Potent and Selective M3 Muscarinic Acetylcholine Receptor Antagonists and Weak Inverse Agonists - Fischer, Oliver; Hofmann, Josefa; Rampp, Hannelore; Kaindl, Jonas; Pratsch, Gerald; Bartuschat, Amelie; Taudte, Verena; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2020)
Muscarinic M-3 receptor antagonists and inverse agonists displaying high affinity and subtype selectivity over the antitarget M-2 are valuable pharmacological tools and may enable improved treatment of chronic obstructive pulmonary disease (COPD), asthma, or urinary incontinence. On the basis of known M-3 antagonists comprising a piperidine or quinuclidine unit attached to a biphenyl carbamate, S-fluoro substitution was responsible for M-3 subtype selectivity over M-2, while 3'-chloro substitution substantially increased affinity through a sigma-hole interaction. Resultantly, two piperidinyl- and two quinuclidinium-substituted biphenyl carbamates OFH243 (13n), OFH244 (13m), OFH3911 (14n), and OFH3912 (14m) were discovered, which display two-digit picomolar affinities with K-i values from 0.069 to 0.084 nM, as well as high selectivity over the M-2 subtype (46- to 68-fold). While weak inverse agonistic properties were determined for the biphenyl carbamates 13m and 13n, neutral antagonism was observed for 14m and 14n and tiotropium under identical assay conditions.
CRIS-Team WoS Importer:2020-05-15